Folkloric Healthcare in Buldhana District of Maharashtra (India) - U.P. Aher, Patil D.A.* and (Journal of Phytology, 2011)
The tribal and most rural folks belong to ‘have-nots’ and modern healthcare facilities are beyond their reach. They have perforce been still using the plant species in their ambience. The objective of the present investigation was to tap down indigenous ethnomedicinal knowledge. Regular field trips were conducted to interview, discuss and document their medicinal knowledge. Actual observations were also made during our ethnobotanical forays. Five informants at least were consulted for each claim and verified on subsequent visits. This investigation brought to light that tribal and rural people of Buldhana district utilize 55 plant species belonging to 37 families. They are beneficial in combating vast array of diseases and disorders covering almost all systems of human body. This paper communicates 61 use-reports, their botanical analysis, highlights common diseases in the study area and discusses origin of medicine in the perspective of doctrine of signatures. Further scientific investigations may help reveal biomolecules useful for human welfare. Key words: Folkloric healthcare, Ethnomedicine, Buldhana district, Maharashtra <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Patil D.A. and Aher U.P. Folkloric Healthcare in Buldhana District of Maharashtra (India). J Phytol 2/12 (2010) 01-08.